Converging lines Eva Hesse and Sol LeWitt - Roberts, Veronica; Lippard, Lucy R.; Swenson, Kirsten (Blanton Museum of Art in association with Yale University Press, 2014)
"Eva Hesse and Sol LeWitt formed a close friendship between the late 1950s and Hesse's death in 1970. Converging Lines celebrates this friendship and offers an illuminating look at their close-knit New York circle. Whereas previous scholarship has examined LeWitt's impact on Hesse, this is the first publication to demonstrate that the artists influenced each other's art and lives in reciprocal and profound ways. Richly documented, this book includes a personal recollection by Lucy R. Lippard, a distinguished American art writer and critic who was a close friend of both artists. Also included are reproductions of 39 postcards LeWitt wrote to Hesse during his international travels, along with a poignant five-page letter that he sent Hesse, attesting to his belief in her talent; a previously unpublished interview from 2001 with LeWitt about his relationship with Hesse; and an illustrated chronology drawing upon interviews, photographs, and primary documents from the time. Shedding new light on the careers and personal lives of Hesse and LeWitt, this publication explores the deep connections between two of the 20th century's most important artists.'--Publisher's website.